Immunogenicity of heterologous H5N1 influenza booster vaccination 6 or 18 months after primary vaccination in adults: A randomized controlled clinical trial. Issue 4 (15th January 2015) - Langley, Joanne M.; Frenette, Louise; Jeanfreau, Robert; Halperin, Scott A.; Kyle, Michael; Chu, Laurence; McNeil, Shelly; Dramé, Mamadou; Moris, Philippe; Fries, Louis; Vaughn, David W.
Highlights We compared an AS03-adjuvanted H5N1 vaccine at different dose levels to placebo. We compared the effect of a vaccine boost 6 or 18 months later with a different strain than the priming strain. Boosting 6 or 18 months later results in rapid and durable immune responses.